Gender Stereotypes in a Children's Television Program: Effects on Girls' and Boys' Stereotype Endorsement, Math Performance, Motivational Dispositions, and Attitudes - Wille, Eike; Gaspard, Hanna; Trautwein, Ulrich; Oschatz, Kerstin; Scheiter, Katharina; Nagengast, Benjamin (Frontiers in Psychology, 2018)
Television programs are a central part of children’s everyday lives. These programs often transmit stereotypes about gender roles such as “math is for boys and not for girls.” So far, however, it is unclear whether stereotypes that are embedded in television programs affect girls’ and boys’ performance, motivational dispositions or attitudes. On the basis of research on expectancy-value theory and stereotype threat, we conducted a randomized study with a total of 335 fifth-grade students to address this question. As the experimental material, we used a television program that had originally been produced for a national TV channel. The program was designed to show children that math could be interesting and fun. In the experimental condition, the program included a gender stereotyped segment in which two girls who were frustrated with math copied their math homework from a male classmate. In the control condition, participants watched an equally long, neutral summary of the first part of the video. We investigated effects on boys’ and girls’ stereotype endorsement, math performance, and different motivational constructs to gain insights into differential effects. On the basis of prior research, we expected negative effects of watching the stereotypes on girls’ performance, motivational dispositions, and attitudes. Effects on the same outcomes for boys as well as children’s stereotype endorsement were explored as open questions. We preregistered our research predictions and analyses before conducting the experiment. Our results provide partial support for short-term effects of gender stereotypes embedded in television programs: Watching the stereotypes embedded in the video increased boys’ and girls’ stereotype endorsement. Boys reported a higher sense of belonging but lower utility value after watching the video with the stereotypes. Boys’ other outcome variables were not affected, and there were also no effects on girl’s performance, motivational dispositions, or attitudes. Results offer initial insights into how even short segments involving gender stereotypes in television shows can influence girls’ and boys’ stereotype endorsement and how such stereotypes may constitute one factor that contributes to gender differences in the STEM fields.